Investigation of Plasma Arc Cutting Parameters With Type-2 Fuzzy Set and System - Celik, Yahya Hisman; Ozek, Muzeyyen Bulut; Ozek, Cebeli (Carl Hanser Verlag, 2013)
The objective of the present study was it to design a type-2 fuzzy set and system in order to predict surface roughness and hardness depending on the parameters (material thickness, cutting speed, arc voltage and current) of the plasma arc cutting process of S235JR sheet materials. Therefore, some experimental studies were conducted. The experimentally determined data were used to describe the type-2 fuzzy set and system. Type-2 fuzzy set and system was found to be usefull to predict surface roughnes and hardness. According to the obtained values, the best surface roughness and the values closest to the hardness of the raw material were obtained at 1500 mm/min cutting speed, 8 mm material thickness, 115 V arc voltage and 80 A current.